2006
DOI: 10.1051/0004-6361:20065688
|View full text |Cite
|
Sign up to set email alerts
|

Transition region counterpart of a moving magnetic feature

Abstract: Context. While moving magnetic features have been studied extensively at the photospheric level, the effect they have on the upper atmosphere remains largely unknown, and it is this which we seek to address in this work. Aims. In this work we aim to investigate the chromospheric and transition-region dynamics associated with a moving magnetic monopole by using spectral time-series and images. Methods. Cross correlation was applied to images taken by different instruments and at different times in order to spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Chromospheric LOS velocity derived from the Ca ii core shift also shows variations on various time scales from upflows to downflows. This fact, together with the variable intensity enhancement observed in Ca ii frames, might suggest the presence of traveling waves (Lin et al 2006). This issue will be investigated in a subsequent study.…”
Section: Type N Featuresmentioning
confidence: 84%
“…Chromospheric LOS velocity derived from the Ca ii core shift also shows variations on various time scales from upflows to downflows. This fact, together with the variable intensity enhancement observed in Ca ii frames, might suggest the presence of traveling waves (Lin et al 2006). This issue will be investigated in a subsequent study.…”
Section: Type N Featuresmentioning
confidence: 84%
“…Thus, currently it is difficult to validate the existence of these strong internetwork magnetic elements above the photosphere. However, in an active region Lin et al (2006) found a correlation between localized emission enhancement above the photosphere (in the chromosphere and TR) and a moving magnetic feature, which followed the boundary of a supergranulation cell. Zhang & Zhang (2000) analyzed quiet-Sun photospheric and chromospheric magnetograms observed by the vector video magnetograph at Huairou Solar Observing Station, and found that all visible variations in the photosphere had corresponding variations in the chromosphere, although the Hβ line, which they used to derive the chromospheric magnetogram, are complicated and may include signals from both the photosphere and chromosphere.…”
Section: Magneto-convection In the Chromospherementioning
confidence: 88%
“…Nye et al (1984) reported a case in which the MMF is clearly associated with a bright feature in the Ca II K line wing but is undetectable in the K line core, implying that the erupting magnetic flux loop associated with this MMF must lie in the low chromosphere. However, Lin et al (2006) found an MMF associated with a bright patch both in the chromosphere and the transition region. Concerning the association between the MMF and the chromospheric jet, Morita et al (2010) identified a case showing that a chromospheric anemone jet may be caused by anMMF colliding with the preexisting magnetic flux.…”
Section: Introductionmentioning
confidence: 91%